Pengaruh PAD, DAU, DBH, dan Belanja Modal terhadap PDRB dan Kemiskinan di Kabupaten Sidoarjo - Priambodo, Aln Pujo; Hidayat, Nur Wahyu (JURNAL MANAJEMEN KEUANGAN PUBLIK, 2024)
The purpose of this study is to determine the impact of Regional Own Generated Funds (PAD), General Allocation Funds (DAU), Revenue Sharing Funds (DBH), and local government capital expenditures on economic growth (PDRB) and poverty levels in Sidoarjo Regency. This research utilizes multiple linear regression analysis method through SPSS software version 25 in data processing. The PAD, DAU, DBH, capital expenditure, GRDP, and poverty data used in this study are taken within period of 2014 to 2020. The results of the study showed that PAD, DAU, DBH, and capital expenditure together did not have a significant effect in increasing economic growth. However, partially, PAD has a significant positive impact on economic growth while DAU, DBH, and capital expenditures have no significant effect even though they affect GRDP growth. In the poverty model, the results show that PAD, DAU, DBH, and local government capital expenditures, either simultaneously or partially, do not have a significant impact in reducing poverty levels in Sidoarjo Regency.